2022
DOI: 10.33988/auvfd.843049
|View full text |Cite
|
Sign up to set email alerts
|

The effects of adding waste sesame seeds to diets on performance, carcass characteristics, and meat fatty acid composition of Karayaka lambs

Abstract: This study aims to determine the effects of the inclusion of waste sesame seed (WSS) to concentrate feed on performance, carcass characteristics, and meat fatty acid profile of Karayaka lambs. A total of twenty-three lambs were randomly allocated to a control group (11 lambs, with an average live weight of 23.39±0.58 kg) and an experimental group (12 lambs, with an average live weight 23.55±0.41 kg). Also, each of the group was divided into two subgroups according to their gender. The lambs were fed with isoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Likewise, our findings were similar to work conducted by de Araújo et al (12) who reported heavier hot and cold carcass weights in intact and castrated Morada Nova lamb males than females. In contrast, Klupsaite et al (28), Sabbioni et al (41) and Kaya et al (26) reported similar hot and cold carcass weights between sexes in lambs. However, Sadeghi et al (42) observed a significant greater hot carcass weight in males than female with comparable cold carcass weights and dressing percent.…”
Section: Carcass and Non-carcass Partsmentioning
confidence: 90%
“…Likewise, our findings were similar to work conducted by de Araújo et al (12) who reported heavier hot and cold carcass weights in intact and castrated Morada Nova lamb males than females. In contrast, Klupsaite et al (28), Sabbioni et al (41) and Kaya et al (26) reported similar hot and cold carcass weights between sexes in lambs. However, Sadeghi et al (42) observed a significant greater hot carcass weight in males than female with comparable cold carcass weights and dressing percent.…”
Section: Carcass and Non-carcass Partsmentioning
confidence: 90%
“…Drawing a connection to this composition, the incorporation of sesame hulls in lamb diets (100 and 200 g/kg feed, respectively) improved the final weight and carcass characteristics, but led to similar meat oxidative stability and fatty acid profiles [ 144 ]. However, in another study, the effects of using sesame seed waste did not affect the growth performances nor the carcass characteristics of Karayaka lambs [ 145 ].…”
Section: Alternative Feed Resources and Small Ruminants’ Product Qualitymentioning
confidence: 99%